Robotics and Mechatronics Proceedings of the 4th IFToMM International Symposium on Robotics and Mechatronics - Zeghloul, Saïd; Laribi, Med Amine; Gazeau, Jean-Pierre (Mechanisms and Machine Science, 2016)
This volume contains papers that have been selected after review for oral presentation at ISRM 2015, the Fourth IFToMM International Symposium on Robotics and Mechatronics held in Poitiers, France 23-24 June 2015. These papers  provide a vision of the evolution of the disciplines of robotics and mechatronics, including but not limited to: mechanism design; modeling and simulation; kinematics and dynamics of multibody systems; control methods; navigation and motion planning; sensors and actuators; bio-robotics; micro/nano-robotics; complex robotic systems; walking machines, humanoids-parallel kinematic structures: analysis and synthesis; smart devices; new design; application and prototypes. The book can be used by researchers and engineers in the relevant areas of robotics and mechatronics.